TIGA FASE NISBAH HUKUM GEREJA DENGAN HUKUM SIPIL - Binawan, Andang (Faculty of Law, Parahyangan Catholic University, 2022)
This paper discusses the changing relationship between canonic law and state (civil) law in history. In general, we can discern three stages: domination, confrontation-conflic and lastly harmony. The stages are marked by theories or principles describing or justifying the current situation. Pope Gelasius, for instance, forward the double sword principle. With the advent of nation-states and emerging scientific approach to reality, we enter the confrontation stage between Church Law and positive secular laws made by nations states. The third stage is marked by the 2nd Vatican Council, putting forward two important principles, i.e., salus animarum suprema lex and salus populi suprema lex, determining the relationship between Church law and secular laws.